2013
DOI: 10.1007/s10815-013-9962-8
|View full text |Cite
|
Sign up to set email alerts
|

Sperm selection using magnetic activated cell sorting (MACS) in assisted reproduction: a systematic review and meta-analysis

Abstract: Purpose To determine whether the use of Magnetic Activated Cell Sorting (MACS) as a sperm selection technique improves ART success rates in couples undergoing assisted reproduction treatment. Methods Systematic review and meta-analysis of prospective randomized trials. Two reviewers conducted study selection and data extraction independently. Results Five studies (prospective randomized trials) that comprised 499 patients were included. Sperm selection using MACS resulted in statistically significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 39 publications
4
66
0
3
Order By: Relevance
“…Several authors previously reported similar results in fertilization rates [15,16,53], embryo quality [17,18], pregnancy rates [18,20,[53][54][55], and additionally healthy infants who are born with normal neonatal assessments [53,[56][57][58].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Several authors previously reported similar results in fertilization rates [15,16,53], embryo quality [17,18], pregnancy rates [18,20,[53][54][55], and additionally healthy infants who are born with normal neonatal assessments [53,[56][57][58].…”
Section: Discussionmentioning
confidence: 68%
“…On the other hand, Gil et al [20] showed that the implantation and miscarriage rated did not vary between MACS or standard sperm selection methods; however, they did observe an improvement in pregnancy rates.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…They suggested that not all species are suitable for MACS separation method. In our knowledge, most of the research for MACS separation or the combination of DGC and MACS used human samples (de Vantéry Arrighi, Lucas, Chardonnens, & De Agostini, 2009;Gil, Shalom, Sivira, Carreras, & Checa, 2013;Martin et al, 2017;Romany et al, 2017). DGC has been proven to effectively remove nonviable spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetophoretic techniques, also referred to as magnetic-activated sorting methods, have been thoroughly described for cells utilizing adhesion-based microfluidic cell-sorting devices in a recent review [54]. Magnetic-activated cell sorting (MACS) is a technique in which paramagnetic or superparamagnetic particles (e.g., beads) are used to improve the efficiency of cell sorting [55]. Particles, favorably monodisperse magnetic beads, are coated with antibodies with specific affinity to cell surface antigens of interest to catch targets.…”
Section: Electric Field-affected Flowsmentioning
confidence: 99%